A Quantum Repeater Sandbox with Warm Atomic Memories and Quantum Dot Photon Sources - Li, Michael (University of Waterloo, 2024)
Quantum communication is known to offer many advantages, including opportunities for distributed quantum computing and more secure information transfer through quantum key distribution. This thesis provides background on how a quantum communication network can be achieved using quantum repeaters and how these components can be constructed with a hybrid system involving a quantum dot source and warm atomic memory. It also presents three experimental projects to realize critical components to the repeater: (1) The quantum dot photon source characterizations and tuning. (2) A compact 3D printed opto-mechanical laser locking board. (3) Optical memory observed in room temperature Cs vapor cells with an EIT memory scheme. These projects have built the basic foundation to create a repeater node using room temperature vapor cells and open the doors to future investigations of warm cell experiments.